Determination of Heart Tumor Foci in Pets and Clinical Results - TOKER , Melahat (MAS Journal of Applied Sciences, 2024)
To evaluate echogenic increases in the heart chambers (cardiac tumor-myxoma) in domestic animals with echocardiography and to share the results. Different images were obtained from dogs and cats that came to veterinary clinics between 2001 and 2024 for echocardiography. For the echocardiography study, a cat-dog cardiac probe was used and the images were recorded with a color printer device. In cardiac studies, especially in dogs, most intracardiac echogenic foci were unilateral, but bilateral echogenic increases were observed. Although the left atrium was the most common location, rare images were observed in the right atrium. The origin of the tumor was determined on echocardiography and medical treatment was given first. The patient’s relatives were told that if medical treatment did not respond, the tumor would have to be removed. Some of our patients with cat and dog cardiac tumors responded to treatment. Our dog, who had left and right atrium biatrial myxoma, seemed to be fine with medical treatment at first, but later died in a short time. Two cats with left atrial myxoma died after one year. Our cats and dogs, which are still being followed, are prolonging their lives as their other cardiac problems respond to treatment.